Batch cultivation of marine microalgae Nannochloropsis oculata and Tetraselmis suecica in treated municipal wastewater toward bioethanol production - Reyimu, Zubaidai; Ozcimen, Didem (ELSEVIER SCI LTD, 2017)
Algae have come into prominence over the last decade as a commercial biofuel feedstock due to their high production efficiencies compared to first and second feedstocks. However, algal investment is not economically feasible currently due to the operational and capital cost. There is still need for innovations for both high productivity and green productions. In order to decrease the cost of the algal processes, usage of some wastes as cultivation medium for algal productions and novel biofuel production methods should be considered according to green chemistry principals. In this study, seawater and wastewater supplied from Istanbul Water and Sewerage Administration (ISKI) were used and combined at different ratios to be utilized as a growth medium for Nannochloropsis oculata and Tetraselmis suecica microalgae strain under the same growth conditions, and its effect on cell proliferation and growth kinetics were investigated. It was found that, both N. oculata and T. suecica can tolerate and utilize the wastewater and, the specific growth rate of the cultures can up to 0.5430 d(-1) (75% of wastewater) for N. oculata and 0.4778 d(-1) (25% of wastewater) for T suecica. Different concentrations show different results for the growth of two species due to the effect of higher concentrations of the fundamental sources on growth stage and change of ionic composition of the culture medium. To evaluate bioethanol production performance of these two strains, samples which included maximum carbohydrate content as well as control groups were chosen for further studies. The results showed that T. suecica is much suitable for ethanol production using municipal wastewater as a culture medium. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Nannochloropsis oculata; Tetraselmis suecica; Wastewater; Microalgae; Bioethanol; BIOCHEMICAL-COMPOSITION; GROWTH; BIODIESEL; SALINITY; BIOMASS; BIOFUEL; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology